Personal, Socio-Economic and Psychological Characteristics of Crossbred Cattle Owners of Surat District in South Gujarat (Indian Journal of Animal Production and Management, 2024)
A study was conducted to know the personal, socio-economic and psychological characteristics of  crossbred cattle owners of Surat district in south Gujarat. A sample of 120 respondents was selected  for the study. The findings of the study revealed that majority of the respondents belonged to middle  age group and were educated up to primary level. In the study area, most of the crossbred cattle  owners were engaged in animal husbandry and agriculture as their main occupation and had medium  dairy farming experience. More than half of the crossbred cattle owners were untrained and belonged  to medium annual income category. Majority of the crossbred cattle owners owned medium sized  herd. Majority of the respondents had medium level of extension contact, organisational participation,  mass media exposure, risk orientation, innovation proneness, economic motivation and market  orientation.
Keywords: Crossbred cattle owners; Surat district; personal characteristics